Study on the expression level of NF-κB and clinical evaluations in spinal tuberculosis patients - Li, TongLin; Bian, HengJie; Wang, Rui; Lu, WanLi; Ma, Yong; Ji, Hui (Cellular and Molecular Biology, 2022)
Spinal tuberculosis or tuberculous spondylitis is one of the most common types of skeletal tuberculosis. Complications of the spine and spinal cord tuberculosis include destruction of the vertebrae, deformity, and paraplegia. Since in some patients, the clinical manifestations of tuberculosis are unusual and timely diagnosis and treatment of this disease can prevent its serious consequences, so in the present study, some cases of rare manifestations of tuberculosis were investigated. The expression of the NF-κB gene in these patients was also evaluated. In this regard, 36 patients with spinal tuberculosis and 30 healthy individuals (as a control group) were assessed. Clinical symptoms, imaging, laboratory tests, pathology, and response to treatment related to patients with spinal tuberculosis and spinal cord tuberculosis were evaluated. NF-κB expression was also evaluated using the PCR technique in peripheral white blood cell samples. The obtained results were analyzed using SPSS ver. 16, χ2 and T-test statistical methods. Mann-Whitney U test and Kruskal–Wallis non-parametric tests were used to analyze non-parametric data. The results showed that out of 36 cases of spinal tuberculosis, 29 cases had spinal tuberculosis, five cases had tuberculous radiculomyelitis, one case had spinal intramedullary tuberculoma, and one case had syringomyelia. 52.78% of patients were male, and 70% of cases were observed between the ages of 35 and 55 years. Fever and back pain were seen in more than 80% of cases. The study of NF-κB expression in the control and case groups showed that the NF-κB expression in the case group increased compared to the control group. This increase was statistically significant (P = 0.0071). In general, in the present study, the methods of clinical diagnosis of spinal tuberculosis were evaluated. Also, the amount of NF-κB transcription factor was evaluated as an effective genetic factor in the diagnosis of this disease.